R for data science : import, tidy, transform, visualize, and model data - Wickham, Hadley; Grolemund, Garrett (O'Reilly, 2017)
"This book introduces you to R, RStudio, and the tidyverse, a collection of R packages designed to work together to make data science fast, fluent, and fun. Suitable for readers with no previous programming experience"--